2021
DOI: 10.4081/or.2020.8549
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty in patients with slipped capital femoral epiphysis: a systematic analysis of 915 cases

Abstract: There is limited evidence on the outcomes of Total Hip Arthroplasty (THA) in Slipped Capital Femoral Epiphysis (SCFE) patients. This systematic review aims to evaluate the current literature in terms of survival rate, functional outcomes, complications and types of implants of THA in SCFE patients. Following the established methodology of PRISMA guidelines, PubMed, Cochrane library, ScienceDirect and Ovid MEDLINE were systematically searched from inception to September 2018. The search criteria used were: (“to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In SCFE, the epiphysis, or head of the femur slips down and backwards off the neck of the bone at the growth plate. SCFE is the most common hip disorder affecting the adolescent population, with a reported annual incidence of 8.8 to 10.8 per 100,000 children aged 9 to 16 years [1,2] . SCFE is known to affect boys more often than girls.…”
Section: Historymentioning
confidence: 99%
See 3 more Smart Citations
“…In SCFE, the epiphysis, or head of the femur slips down and backwards off the neck of the bone at the growth plate. SCFE is the most common hip disorder affecting the adolescent population, with a reported annual incidence of 8.8 to 10.8 per 100,000 children aged 9 to 16 years [1,2] . SCFE is known to affect boys more often than girls.…”
Section: Historymentioning
confidence: 99%
“…Slipped capital femoral epiphysis (SCFE) is the most common hip disorder affecting the adolescent population, with a reported annual incidence of 8.8 to 10.8 per 100,000 children aged 9 to 16 years [1,2] . SCFE is known to affect boys more often than girls.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There have been a few studies that examined the impact of age in adolescents with SCFE, surgically treated with PIS, in predicting symptomatic FAI and therefore, worse functional outcomes (10)(11)(12). Most of them showed that age >12 years might be associated with an elevated risk, although this result exhibited only a tendency.…”
Section: Groupmentioning
confidence: 99%